(3GdebGUO GdSfjI aj GdCMGOjK GdEdgjI heG GVja EdjgG ef GdMcGjGJ GdhYXjI hGdCTYGQ GdRgOjIs - (3GHf HdHGf , Ydj Hf HdHGf Hf YHO Gddg, YdGA GdOjf (B- (3CHh GdMSf,J (B739 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdcdeI GdYdjI hHYO aEf CaVd GdYdhe HYO GdcJGH GdYRjR hbO NQL GdYHO GdabjQ gPg GdeGjI MOjK GdEdgjI eeG jQhjg GdfHi Udi Gddg Ydjg hSde Yf LHQjd s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3CHh YHO Gddg eMeO Hf CMeO Hf YeQ GdMfai ef bUjOI jeOM HgG QShd Gddg Udi Gddg Ydjg hSde hLYdJg ehdi dcd ehMO HhdGjI jfLh Gdhdi hjfLH s
(3QhGjI GHh GdaOG GSeGYjd Hf YeQ Hf GdefPQi GdMehi s
(3HChdg JedcGJ s
(3Jcde ai gPG GdcJGH Yf eFI MOjKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B267 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B48s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs